Prognostic Impact of the Angiogenic Gene POSTN and Its Related Genes on Lung Adenocarcinoma - Sun, Dongfeng; Gai, Zhibo; Wu, Jie; Chen, Qingfa (Frontiers in Oncology, 2022)
Angiogenesis is a hallmark of cancer and performs a fundamental role in lung cancer progression. However, the function of angiogenesis-related genes (ARGs) in lung adenocarcinoma (LUAD) remains poorly documented. This study was designed to reveal the action and mechanism of ARGs in LUAD. We worked with sequencing data and clinical information for LUAD from public databases. WGCNA was performed to mining hub genes associated with the above genes and functional enrichment analysis was executed. Cox regression analyses were run to construct prognostic gene labels based on the results of the K-M analysis. POSTN and microvessel density were detected by immunohistochemistry and their correlation was analyzed. Estimation of Stromal and Immune cells were employed to profile alterations in the immune microenvironment. Competing endogenous RNA network was structured based on the prognostic genes. We identified POSTN was closely associated with survival of LUAD patients. We constructed a prognostic gene signature, which could also serve as an independent prognostic marker for LUAD. ESTIMATE and CIBERSORT analyses suggested that our risk scoring system may be implicated in altering the immune microenvironment of LUAD patients. A ceRNA network was constructed based on prognostic genes. The genetic signature of POSTN was implicated in the clinical outcome of LUAD patients. A novel prognostic genes signature associated with ARGs was constructed , which may alter the immune microenvironment and ultimately affecting the survival of LUAD patients.